Produktivitas Jamur Merang (Volvariella volvaceae ) Pada Media Campuran Batang Jagung dan Jerami Padi yang Ditanam dalam Baglog Dan Keranjang - Anggraini, Bella Elma; , Dra.Suparti, M.Si (2017)
Corn stalks are agricultural wastes that have a cellulose content, pentose and lignin can be used as a growing medium for mushroom. The purpose of this study to determine the effect of corn stalks in a variety of media concentration, the effect of planting baglog and raised beds, and corn stalks media interaction in various concentrations by planting in raised beds on productivity baglog and mushroom. This study was prepared by a completely randomized design (CRD) with two factors and three replications. Factor 1 concentration of corn stalks (J1) 125g, (J2) 250g, (J3) 375g, (J4) 500g. Factor 2 planting: (U) beds, (B) baglog. The parameters measured were the number of fruiting bodies and edible mushroom fruit body weight. Data were tested by ANOVA analysis of two paths. Based on the analysis of variance showed that the addition of different concentrations of corn stalks media by planting in raised beds and baglog give effect to the number of fruiting bodies and edible mushroom fruit body weight The best treatment for a number of fruiting bodies is UB2 is 34 fruit body, while the lowest treatment is BJ4 ie 7,7 fruit body. The best treatment for body weight of the fruit is UB0 ie 623,4 g, while the lowest treatment BJ4 namely 146,6 g. Keywords:Baglog, baskets, mushroom productivity, stalk corn